Practicing positive psychology coaching : assessment, activities, and strategies for success - Biswas-Diener, Robert. (Wiley, 2010)
"This practical guide reports the latest positive psychology research findings and offers specific, detailed explanations of coaching interventions from a positive psychology perspective. Each intervention is clearly outlined and, where appropriate, illustrated by case studies from organizational and life coaching. Filled with reflective exercises, this book enables positive psychologists and coaches to enhance their own development and, ultimately, to grow their practices."--